Offense-Related Issues in Forensic Psychiatric Treatment: A Thematic Analysis - Askola, Riitta; Soininen, Päivi; Seppänen, Allan (Frontiers in Psychiatry, 2020)
Characteristics unique to forensic psychiatric treatment include coming to terms with the offences committed, the long duration of treatment and the assessment of the risk of repeat offending. This study describes the views of both patients and staff on the significance of the patient’s offence as a part of forensic psychiatric rehabilitation. Eight forensic psychiatric patients and eight forensic psychiatric nurses from two forensic psychiatric hospitals in Finland participated in this study. Data was gathered by means of thematic interview and analysed by means of thematic analysis. The findings suggest that patients and professionals alike concur that ascertaining the factors with a bearing on the offence, and working through the offence and the factors leading up to it, constitute an essential aspect of forensic treatment. This, in turn, has a bearing on the planning and administration of a treatment plan consisting of both medical and psychosocial support and interventions intended to enable patients to live independent, fulfilling lives, thus reducing the likelihood of reoffending. The findings of this study can be used as part of the development of international, standardized treatment models for clinical forensic psychiatric practices.